Antioxidant and Anti-Angiogenesis Properties of Aristolochia Maurorum Using Ex Vivo, In Vitro, and In Vivo Studies - shamel, batool; sahib, hayder baha (Journal of Pharmacology and Drug Development, 2026)
ObjectiveThis study seeks to examine the anti-angiogenic characteristics of Aristolochia maurorum seed extract through various methodologies, including the extraction process, rat aortic ring assay, chorioallantoic membrane (CAM) assay, and DPPH assay for antioxidant assessment.